The Influence of Perceived Quality, Perceived Value of Cost, Brand Identification, and Brand Trust on Brand Loyalty Mediated by Customer Satisfaction in Batam City - Engelina, Jerly; Laulita, Nasar Buntu (Jurnal Maksipreneur, 2024)
Due to technology steadily developing at a rapid pace, it gave rise to many new businesses one of which is smartphone products. This study aims to analyze the effect of perceived quality, perceived value of cost, brand identification, trust, and lifestyle congruence on brand loyalty mediated by customer satisfaction with using Samsung smartphones in Batam City. The sample size was 378 respondents using purposive sampling. Empirical data was obtained through the distribution of online questionnaires with Google Forms. Testing research data using Structural Equation Modeling, Smart PLS 3 software. The results confirm that variables perceived quality, perceived value of cost, brand identification, and brand trust have a significant positive effect on customer satisfaction. The perceived value of the cost value variable, brand identification, and customer satisfaction have a significant positive impact on the brand loyalty variable. In contrast of the perceived quality variable, brand trust has no significant effect on brand loyalty. The variables perceived quality, perceived cost value, brand identification, and brand trust have a significant positive impact on brand loyalty mediated by customer satisfaction. The purpose of this research is to contribute to literature and marketing strategies to be more efficient as a decision-making tool in companies.